Utilization of basic diabetes mellitus services among adult patients with diabetes mellitus at Mbarara Regional Referral Hospital diabetes clinic, Uganda: a cross-sectional study - Muramuzi, Dan; Mugambe, Richard; Muteebwa, Laban; Albert, Ipola Patrick; Nduhukyire, Lawrence; Nnannyanzi, Claire; Mukose, Aggrey David (Frontiers in Clinical Diabetes and Healthcare, 2024)
BackgroundUtilization of diabetic care services remains a challenge among adult patients in low- and middle-income countries. Optimal utilization of diabetic care services could reduce morbidity and mortality and delay the development of long-term complications. This study assessed the utilization of basic diabetic care services and associated factors among diabetes mellitus patients at Mbarara Regional Referral Hospital in Western Uganda.MethodsWe enrolled 208 patients with either type 1 or 2 diabetes mellitus in a cross-sectional study between June and August 2022 at Mbarara Regional Referral Hospital, Uganda. Consecutive sampling was used to select patients with diabetes mellitus who attended the diabetes clinic based on their scheduled date of appointment. Optimal utilization of basic diabetic services was defined as receiving at least three of the four core services: health education, assessment of vital signs (blood sugar, blood pressure, and body mass index), assessment of diabetic complications, and diabetic drug refills. Modified Poisson regression analysis was used to assess the determinants of utilization of basic diabetic services in STATA version 14.0.ResultsThree-quarters of the study participants were female patients (75.0%), and the median (inter-quartile range, IQR) age was 52 (43, 56). Moreover, 62.0% [95% confidence interval (CI): 55.3–68.7] self-reported to have utilized basic diabetic care services. In the adjusted analysis, waiting longer than 120 min to receive any service [adjusted prevalence ratio (aPR) 0.46, 95% CI 0.27–0.80), being 45–54 years old (aPR 1.48, 95% CI:1.11–1.98), and being 55–60 years old (aPR, 1.38, 95% CI: 1.02 1.86)] were significantly associated with the utilization of basic diabetic care services.ConclusionUtilization of basic diabetic care services among adult patients remains sub-optimal. Age and waiting time were significantly associated with the utilization of diabetic care services. Interventions should be directed toward shortening the waiting time in service delivery at diabetes clinics.